Enantioselective nickel-catalyzed intramolecular allylic alkenylations enabled by reversible alkenylnickel E/Z isomerization - Yap, Connor; Lenagh-Snow, Gabriel M.J.; Narayan Karad, Somnath; Lewis, William; Diorazio, Louis J.; Lam, Hon Wai (Wiley-VCH Verlag, 2017)
Enantioselective nickel-catalyzed arylative cyclizations of substrates containing a Z-allylic phosphate tethered to an alkyne are described. These reactions give multisubstituted chiral aza- and carbocycles, and are initiated by the addition of an arylboronic acid to the alkyne, followed by cyclization of the resulting alkenylnickel species onto the allylic phosphate. The reversible E/Z isomerization of the alkenylnickel species is essential for the success of the reactions.